IDEOLOGÍA DE GÉNERO - Latorre Ariño, Marino (2019)
This article deals with gender ideology and the historical process that has brought it to life; it also considers the main ideologists of such ideology. It defines some concepts related to gender ideology, its purpose, and the international organisations and private entities that promote, foster and finance it in the world. It refers as well to the organisations opposed to this ideology and the reasons that they advocate for it. It offers some language clarification about gender ideology and includes some scientific information about the topic. Before conclusion, it presents collateral issues related to homosexuality. The conclusion is a word of warning to the readers about this ideology.